Pengelolaan Pengembangan Objek Wisata Sejarah Benteng Marlborough di Kota Bengkulu - Amalia, Anisa; Mubarak, Adil (PUBLICNESS: Journal of Public Administration Studies, 2024)
This examination is spurred by the not exactly ideal administration of the authentic vacation spot Post Marlborough in the city of Bengkulu. This exploration utilizes graphic subjective examination. The point of this examination is to decide the administration of the advancement of the authentic vacation spot Post Marlborough in the city of Bengkulu. The aftereffects of the examination show that: the management of the historical tourism development of Fort Marlborough in the city of Bengkulu using the "POAC" approach, namely planning, organizing, actuating and controlling, has been running optimally, meaning that management is carried out using a collaborative approach process (Collaboration Planning in Coastal Tourism development), coordinating every source. human resources in the tourism office to work in accordance with their respective fields and carry out outreach with the community, as well as work with the Region VII cultural preservation center in management. So you can optimize inspections directly or via online media to monitor all activities.